Islamic justification of foreign exchange options contract as a tool of risk management - Azlin Alisa, Ahmad; Mustafa' Afifi, Ab. Halim; Nadhirah, Nordin (2015)
Foreign Exchange options contract (FX options) is known as an agreement in which a seller (writer) conveys to a buyer (holder) the right but not the obligation to buy or sell a specific quantity of a currency at a specified price on or before a specified date. This should be considered as an efficient contract as it can help to eliminate the risk of fluctuating exchange rates by fixing a rate on the date of the contract for a transaction that will take place in the future. Although, FX options provides facility of risk management, some shariah issues arise, such as issue of riba, gambling, trading of promise and many more. In addition, FX options contract gives the parties an opportunity to gain leverage which is not allowed in Islam. Thus, the aim of this study is to examine Islamic justifications of FX options contract as a tool of risk management. This study finds that, some shariah principles such as bay’ al-urbun, bay’al-inah, wa’d and bay’ al-sarf can be developed to avoid the issue of riba. In order to avoid gambling and leveraging activites, this study suggests that FX option contract should be allowed in the first phase only in a static manner. Consequently, this contract should not be allowed to be practiced in the secondary market as currency trading is clearly prohibited in Islam. In order to make sure that this contract is comply with Shari’ah, this contract must strictly be used only in conjunction with real trades in goods and services.